Off-Label Use in Rare Diseases: Myasthenia Gravis, Lambert-Eaton Myasthenic Syndrome and Congenital Myasthenic Syndromes - Janzen, Rudolf (Neurology International Open, 2018)
The off-label use of licensed drugs is widespread, and the risk of adverse events is elevated, especially if the scientific evidence is low. The treatment of rare diseases (<5/10,000) therefore may increase the risk of off-label use. The optimized standard treatment is primarily based on the regulatory decisions of the German Federal Joint Committee. The valid guidelines and the regulations of the German health system are discussed in this article. The criteria for indication and monitoring of off-label use are shown, especially focused on the problem of refractory myasthenia gravis. Escalation of treatment results regularly in off-label use. The arguments within the applicable guidelines should be followed. Some new aspects of the European regulations are likewise discussed.
Keywords: off-label use; refractory myasthenia gravis; Lambert-Eaton myasthenic syndrome; congenital myasthenic syndrome